PENERAPAN INDEX OF BIOTIC INTEGRITY (IBI) DI SUNGAI CIBARENO - Nestiyanto Hadi (Bioma, 2020)
ABSTRACT The fish assemblage data were collected during August to October 2013 at Cibareno River, which is located in the area of Lebak and Sukabumi. The fish assemblage were analyzed using index of biotic integrity (IBI). The data result were obtained about species richness, IBI metric modification, and IBI cross test with Pesanggrahan River. The fish assemblage that was obtained as many as 22 species from 11 family. IBI metric modification that was defined by Pearson correlation test showed that there was correlation between metrics: herbivor, carnivore, omnivor, benthic species, water column species, long-lived species, tolerant species, intolerant species, native species, non-native species, abundance, and fish condition (disease, fin damage, skeletal anomalies). The IBI total score for cross test with Pesanggrahan River is 46. The total score indicates that Cibareno River is include in the category of a good river. Those condition means that Cibareno River can be worthy as a reference site for IBI. Keywords: IBI, fish richness, reference site, Cibareno River.